Candi dan Taman, Dahulu dan Sekarang - Rita Margaretha Setianingsih (Balai Arkeologi Sumatera Utara, 2007)
AbstractTemple attributed to all building of omission of culture Hindu-Buddha, especially religious holy building. As for garden, farm cultivated by the flower, making people feel the ruthless and freshness, return to think clear and free from the mind disquiet so that do not surprise if garden become the important shares of building complex. Not merely complex temple of a period of Hindu-Buddha in just Nusantara, but later also at palace complex (kraton) in Nusantara, latter and also church. Now even also most observance building equipped by the garden arranged natty. Certain birch planted, beside because its practical function also because symbolic role and function.